Identification Science and Engineering Performance Elementary School Students Using Based LKPD Engineering Design Process - Rohmawati, Ifatur; Putra, Pramudya Dwi Aristya; Rusdianto, Rusdianto (Unnes Science Education Journal, 2023)
Science and engineering performance play an important role in science and engineering education. This study aims to identify science and engineering performance by using LKPD based Engineering Design Process (EDP). This type of research is qualitative using the method case study. Data was collected through observation, interviews and documentation. The validity of the data using triangulation techniques. The results of the study showed that the use of EDP-based worksheets can improve science and engineering performance in elementary school students. Students demonstrate a better understanding of science concepts and techniques and are able to apply them in the EDP included in the LKPD. But some students still think that science concept events are things that are rarely encountered in everyday life. So that students do not understand the science concept that occurs in a water filter. However, students are able to demonstrate the ability to identify problems, design solutions, and evaluate the results they get.